DIPG-25. A KINOME-WIDE shRNA SCREEN UNCOVERS VRK3 AS AN ESSENTIAL GENE FOR DIPG SURVIVAL. Issue 2 (22nd June 2018) - Evangelista, Cláudia CS; Barret, Emilie; Merlevede, Jane; Saccasyn, Ambre; Puget, Stéphanie; Grill, Jacques; Castel, David; Debily, Marie-Anne
Abstract: Diffuse Intrinsic Pontine Glioma (DIPG) remains the most fatal form of pediatric brain tumor. The specific somatic mutation (H3K27M) in the H3 histone gene was found in around 95% of patients making this alteration as the initial oncogenic event. However, until now this alteration cannot be targeted. Consequently, we conducted a RNAi-based loss-of-function screen targeting the human kinome to decipher vulnerabilities in DIPG, unravel their biology and provide therapeutic opportunities in this devastating disease. An integrative lentiviral pooled library of 7450 shRNAs against 770 kinases was used to transduce four GSC (glioma stem cells) cultures harboring either H3.1 (n=2) or H3.3-mutation (n=2) in order to cover the diversity observed in patients, and 2 control NSC (neural stem cell) cultures. The entire set of shRNAs was identified by sequencing 40 hours and 22 days after transduction. Genes required for cell expansion over 22 days of outgrowth in GSC but with limited deleterious effect on NSC proliferation were identified. Among those, we selected the target genes with at least 3 distinct shRNAs presenting a significant decrease in their abundance and identified in particular VRK3 (Vaccinia-Related Kinase 3) as one of the top scoring kinases whose extinction was lethal to DIPG. This serine-threonine kinase was recently linked to cell cycle progression, DNA repair and neuronal differentiation. The role of this protein in DIPG biology is currently assessed especially to identify actionable downstream targets. Drugs mimicking the effect of VRK3 extinction will be evaluated in our vitro and vivo models of DIPG.